Penyuluhan Edukasi Kesehatan Gigi Dan Mulut Kuliah Kerja Nyata (Kkn) Pembelajaran Pemberdayaan Masyarakat Desa Pekik Nyaring Tahun 2024 - Zantika, Ninalia; Murdalena, Reza; Oksidistri, Oksidistri; Tranado, Hengki; Pebriani, Emi (Jurnal Gotong Royong, 2024)
This Real Work Lecture (KKN) seeks to solve various health problems faced by certain communities, especially children at SDN 02 Central Bengkulu. Maintaining oral hygiene is the most important preventive measure recommended to prevent infections that can cause cavities. The solution to this program is the preparation of material delivery and how to overcome the health problem of cavities which often occurs in elementary school children. The form of activity is in the form of health education from lecturers with participants namely elementary school children in class 2 who are the respondents in this activity. Meanwhile, the extension method is carried out by the KKN implementer continuously during the ongoing and programmed KKN program period. During the implementation of this KKN activity, a quiz was also given about the impact of not maintaining healthy teeth and mouth. The output of this KKN is in the form of reports and article publications so that it can be accessed by everyone who needs literature in the form of related articles. Methods: Guidance and counseling before and after counseling students do pre and post test questions. Conclusion: students get increased knowledge about tooth brushing and can re-practice how to brush their teeth. Keywords: tooth brushing, elementary school students